Occupational overuse syndrome and psychosocial stressors in the work place : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, at Massey University - Stephens, Christine (Massey University, 1993)
There is continuing concern about the incidence of Occupational Overuse Syndrome among workers using keyboards in New Zealand, but very little local research into the possible causes of the syndrome. Following results from overseas research, it is hypothesised that differences in rates of pain reporting by keyboard workers are related to job stress caused by different levels in the quality of the work environment. An interaction between autonomy and work pressure is also hypothesised. Keyboard users in several different job types, working in eight different newspaper offices of the same newspaper company, were surveyed. The results confirmed the hypotheses. Post hoc analysis showed that there were important differences between the types of stressors that predicted pain reporting between offices, and those that predicted pain reporting between job types. These results confirm the importance of considering psychosocial factors in work and workplace design for the prevention of OOS. Conclusions are also drawn about the situation specificity of such empirical research, and the need for more theoretical work in the search for the aetiology of OOS.
Keywords: Job stress; Newspaper publishing; Overuse injuries; Work injury prevention; Occupational Overuse Syndrome